Observational study of thrombosis and bleeding in COVID-19 VV ECMO patients. Issue 2 (February 2022) - Ripoll, Brianda; Rubino, Antonio; Besser, Martin; Patvardhan, Chinmay; Thomas, William; Sheares, Karen; Shanahan, Hilary; Agrawal, Bobby; Webb, Stephen; Vuylsteke, Alain
Introduction: COVID-19 has been associated with increased risk of thrombosis, heparin resistance and coagulopathy in critically ill patients admitted to intensive care. We report the incidence of thrombotic and bleeding events in a single center cohort of 30 consecutive patients with COVID-19 supported by veno-venous extracorporeal oxygenation (ECMO) and who had a whole body Computed Tomography Scanner (CT) on admission. Methodology: All patients were initially admitted to other hospitals and later assessed and retrieved by our ECMO team. ECMO was initiated in the referral center and all patients admitted through our CT scan before settling in our intensive care unit. Clinical management was guided by our institutional ECMO guidelines, established since 2011 and applied to at least 40 patients every year. Results: We diagnosed a thrombotic event in 13 patients on the initial CT scan. Two of these 13 patients subsequently developed further thrombotic complications. Five of those 13 patients had a subsequent clinically significant major bleeding. In addition, two patients presented with isolated intracranial bleeds. Of the 11 patients who did not have baseline thrombotic events, one had a subsequent oropharyngeal hemorrhage. When analyzed by ROC analysis, the area under the curve for % time in intended anticoagulation range did not predict thrombosis or bleeding during the ECMO run (0.36 (95% CI 0.10–0.62); and 0.51 (95% CI 0.25–0.78); respectively). Conclusion: We observed a high prevalence of VTE and a significant number of hemorrhages in these severely ill patients with COVID-19 requiring veno-venous ECMO support.